Vulnerabilities of Networked Energy Infrastructure : A Primer - Schweikert, Amy; Nield, Lindsey; Otto, Erica; Klemun, Magdalena; Ojanpera, Sanna; Deinert, Mark (World Bank, Washington, DC, 2019)
Considerable work has been done to understand and improve the resilience of individual infrastructure components. However, systems of components, or even systems of systems, are far less well understood. Cascade effects, where the loss of one infrastructure affects others, is a major source of vulnerability which can lead to catastrophic disruptions of essential services. Interdependencies can also lead to large-scale failures when even a single component is disrupted and results in 'cascading' failures within and between networks. This is particularly true for power systems, as many other lifeline infrastructure systems rely on electricity. In this study we review the literature and give a primer on the vulnerabilities of networked energy infrastructure. Several recurrent themes emerge from across different systems: (1) Electricity is essential for many lifeline infrastructure systems to function; (2) Electrical distribution systems are particularly vulnerable to disruption from natural and manmade hazards; (3) Highly networked systems can be unstable even when their individual components are functioning as intended; (4) Redundancy and network density can increase reliability but also increase the likelihood of cascade effects when failures do occur; (5) Disruption of ports and roads can limit fuel supplies for generators and replacement components. Based on these insights, this study offers suggestions for further research and policy actions.